Investigations Electronic Records Keeping Challenges Faced by the Employees of ABC Company: Basis for Improvement: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Electronic record management systems are essential for organizations to protect and improvetheir efficiency. They involve the professional practice of classifying, organizing, andmanaging documents and records. However, challenges faced by electronic recordmanagement systems include not have own username and password on their PC when itcomes to using the system, outdated information systems, and having only one internetservice provider in the company office that is used in the system. It is important for recordsprofessionals to perform the required scope of responsibilities when implementing theRecords Management System program. Without a records specialist, the entire task would bedifficult for untrained, inexperienced individuals to complete.The level of familiarity, usability and efficiency, accessibility, and effectivity are stronglyagreed upon. Employees should record copies of documents and keep them on an official file,have a staff member in the record and archives office with assigned responsibility to useelectronic document and transaction management systems (EDTMS), browse throughavailable files or folders, and store permanent records with temporary records until they aretransferred for archiving.Electronic record-keeping is essential for any business as it allows for the management of oneof the most crucial resources in any organization. A policy must be developed to govern recordmanagement operations and ensure that all records generated and received are properlydocumented. Additionally, policies should be created and managed by documenting them,assigning roles, and developing formal processes. Finally, secrecy or restricting access toelectronic records must be prevented, and users must be ensured that user records are highlysafeguarded and monitored. The electronic records management life cycle idea must beutilized at all levels of the company, and an acceptable model for the preservation of recordsand data must have been developed.
Keywords: Business